Perencanaan Desain Parkir dan Jalan Akses Menuju Lokasi Wisata Baru di Kadirejo, Karanganom, Klaten - suseno, dhony priyo; Aris Krisdiyanto; Kemmala Dewi; Wahyu Dwi Mardiani (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Geographically, Kadirejo village is located to the south of the Karanganom sub-district capital, which is still an integral part of the Klaten Regency area with a distance of 2 km from the sub-district capital and 7 km from the district capital, while from the provincial capital it is around 100 km. The Kadirejo village government has several parts of land that will have no access due to the closure of the Solo – Jogja toll road. To get around this, the Kadirejo Village Head wants to create a new tourist spot in the form of a Tiban market and fishing pond so that the village remains busy and increases the village's cash fund income through Bumdes. For this reason, the village head collaborated with academics to participate in planning the idea. The purpose of this community service is to help the community provide a brief description of partner problems and the goals of community service. The methods used are field surveys, data processing and reports. The final result is suggestions or recommendations regarding parking patterns and types of access roads to the tourist location in question. The recommended parking pattern is an island parking pattern with a type A fishbone shape (60° angle), and the road type is paving.